How does the portrayal of civilian teacher training schemes affect the appeal of them for military personnel?. Issue 1 (2nd January 2023) - Mather, David
ABSTRACT: The dominant public discourse regarding the recruitment and retention of teachers is one that is often framed in terms such as 'crisis'. Data from the Department for Education, the National Audit Office and bodies such as the Education and Training Foundation highlight challenges in filling vacancies across each part of the education sector. This is particularly acute in subject areas relating to Science, Engineering and Technology (SET). This paper analyses discourses relating to teacher training amongst tri-service personnel in the English context. Sources from publications such as FE Week and CTP (Career Transition Partnership) are addressed. In doing so, the paper compares educational and military sources in order to examine how the representation of a civilian teaching career varies between the two. This is about adding to the wider societal narrative regarding the ways in which military to civilian transition can be aided by the reframing of skills and experience acquired during military service.